El terrorismo en su modalidad de accidente de tránsito aparente - Chamba Viscarra, Xavier Leonardo (2021)
This investigative work seeks to learn a little more about organized crime in aspects that put the internal and external security of the Ecuadorian State at risk, with respect to terrorist acts committed under any modality. As we well know, terrorism in its various forms is presented as a subtle and masked struggle in which each of the parties considers itself an assault. As it is well known, terrorism is not new in the international arena, it constitutes anarchic opposition to the content and form of coexistence of a totally organized and mainly civilized society, for this reason this figure of total anarchy is one of the most important on the agenda. In recent centuries, especially at the end of the 20th century and the beginning of the 21st, this form of extreme violence is closely followed by the main authorities of each nation...........